Community Knowledge and Acceptance of Larviciding for Malaria Control in a Rural District of East-Central Tanzania - Mboera, Leonard E. G. (MDPI, 2014)
The use of microbial larvicides, a form of larval source management, is a less commonly used malaria control intervention that nonetheless has significant potential as a component of an integrated vector management strategy. We evaluated community acceptability of larviciding in a rural district in east-central Tanzania using data from 962 household surveys, 12 focus group discussions, and 24 in-depth interviews. Most survey respondents trusted in the safety (73.1%) and efficacy of larviciding, both with regards to mosquito control (92.3%) and to reduce malaria infection risk (91.9%). Probing these perceptions using a Likert scale provides a more detailed picture. Focus group participants and key informants were also receptive to larviciding, but stressed the importance of sensitization before its implementation. Overall, 73.4% of survey respondents expressed a willingness to make a nominal household contribution to a larviciding program, a proportion which decreased as the proposed contribution increased. The lower-bound mean willingness to pay is estimated at 2,934 Tanzanian Shillings (approximately US$1.76) per three month period. We present a multivariate probit regression analysis examining factors associated with willingness to pay. Overall, our findings point to a receptive environment in a rural setting in Tanzania for the use of microbial larvicides in malaria control.